Analysis of Her2/neu membrane protein clusters in different types of breast cancer cells using localization microscopy - Kaufmann, Rainer; Müller, Patrick; Hildenbrand, Georg Lars; Hausmann, Michael; Cremer, Christoph (Journal of microscopy, 2011)
The Her2/neu tyrosine kinase receptor is a member of the epidermal growth factor family. It plays an important role in tumour genesis of certain types of breast cancer and its overexpression correlates with distinct diagnostic and therapeutic decisions. Nevertheless, it is still under intense investigation to improve diagnostic outcome and therapy control. In this content, we applied spectral precision distance/position determination microscopy, a technique based on the general principles of localization microscopy in order to study tumour typical conformational changes of receptor clusters on cell membranes. We examined two different mamma carcinoma cell lines as well as cells of a breast biopsy of a healthy donor. The Her2/neu receptor sites were labelled by immunofluorescence using conventional fluorescent dyes (Alexa conjugated antibodies). The characterization of the Her2/neu distribution on plasma membrane sections of 176 different cells yielded a total amount of 20 637 clusters with a mean diameter of 67 nm. Statistical analysis on the single molecule level revealed differences in clustering of Her2/neu between all three different cell lines. We also showed that using spectral precision distance/position determination microscopy, a dual colour reconstruction of the 3D spatial arrangement of Her2/neu and Her3 is possible. This indicates that spectral precision distance/position determination microscopy could be used as an enhanced tool offering additional information of Her2/neu receptor status.